Treatment of severe facial asymmetry secondary to osteochondroma of the mandibular condyle: case report - Vale, D Santiago; Araujo, Marcelo Marotta [UNESP]; Cavalieri, Irio; Gabrielli, Mário Francisco Real [UNESP]; Santos, M B Pessoa; Canellas, J V dos Santos (My University, 2011)
Osteochondroma (OC) is the most common benign tumor of long bones. However it is rarely found in the facial skeleton, being the coronoid process and mandibular condyle the most affected sites in this region. It basically consists in bone growth covered by cartilage. The etiology is still controversial: neoplastic, developmental, reparative and traumatic origins have been discussed in literature. The treatments of these lesions include total condylectomy or local resection of the lesion. This paper aims to report a case of a patient with history of trauma and possible fracture of the mandibular condyle in childhood, which in youth developed dentofacial deformity with severe facial asymmetry. The treatment consisted of resection of lesion both with maxillary and mandibular osteotomies associated with graft from the iliac crest bone. Actually, the patient is with a favorable aesthetic, without functional deficit and absence of lesion’s recurrence.
Keywords: Cirurgia Ortognática; Assimetria facial; Osteocondroma